Effects of fluorine modifiers and gold colloids in enhancing photocatalytic activity of TiO2 under visible light irradiation - Zayadi, Rabi’atul ‘Adawiyah (2017)
The process where a light-activated catalyst is used to break down organic contaminant is known as photocatalysis. In the class of photocatalyst, titanium dioxide (TiO2) has isolated itself on top of the list and widely applied in environmental remediation including water treatment. In addition to the worrying release of industrial dye containing organic pollutants that threaten the environment, TiO2 can be utilized to degrade dyes in the wastewater. To tune TiO2 into a better photocatalyst with enhanced photocatalytic activity under visible light irradiation, TiO2 was initially synthesized using peroxotitanic acid (PTA) method using two different solvents of distilled water and Zamzam water. Fluorine was then added into TiO2 to control the crystal phase and morphology of TiO2 nanoparticles which are proven by X-Ray Diffractometer (XRD) and Field Emission-Scanning Electron Microscope (FE-SEM) respectively. Fluorine-modified TiO2 (F-TiO2) revealed to be in single anatase form with the particle shape directed to ovoid shape. Gold nanoparticles (GNP) was also deposited on TiO2, producing Au-TiO2 to enhance the absorption in the visible light region as well to facilitate electron-hole separation. GNP stabilized using Acacia senegal and aloe vera were characterized using Ultraviolet-Visible (UV-Vis) spectrophotometer. Stabilization of GNP was found to be better using Acacia senegal with 2 : 1 weight ratio of stabilizer to gold precursor as compared to aloe vera. The photocatalytic activity of synthesized TiO2 was carried out with 0.04 g/L Reactive Blue 19 dye aided with blue light (475 nm) to activate the photocatalyst. Photocatalysts synthesized from distilled water were found to display higher photocatalytic activity than Zamzam samples. Within 120 minutes of reaction, the highest percentage of degradation of 49.23 % was recorded by Au(AS)/F-P-TiO2 (HF) which was characterized to be anatase, ovoid shape, crystallite size of 30.71 nm and band gap energy of 3.22 eV. The data presented in this study thus recognized the ability of TiO2 to carry out photodegradation of reactive dye in the visible light region with credits given to the action of fluorine and gold for revamping the photocatalytic properties of TiO2.